PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV-A SD NEGERI 13 GAJAH SAKTI KECAMATAN MANDAU KABUPATEN BENGKALIS - Suryani, Erma; Syahrilfuddin, Syahrilfuddin; Hamizi, Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Some of the finding problems in the learning process of science at fourth grade students of SD Negeri 13 Gajah Sakti were: the low of students’ ability in learning science, some students were not active to solve the problems about learned subject by reading. This caused that most students got low score of science examination, 15 students (60%) were able to get 70 as the minimal score of science, but 10 students (40%) only got score below 70. This fact motivated the researcher to conduct the action research to increase the students’ ability in science. The action conducted into two cycles. Each cycle consisted of two meetings. The subject of this research was the fourth grade students of SD Negeri 13 Gajah Sakti. There were 25 students, 14 boys dan 11 girls. The score of the teacher’s activity at first cycle meeting one was 57.0 category less, increased in meeting two to be 64.3 category less. It increased to be 71.4 at the second cycle meeting one, and being 82good at meeting 2. At the first cycle, it was found that only some students learned actively, but at the secondcycle, most students were more active and giving their participation in learning process. The success of this action research can be seen from the students’ result in examination from 62.9 category less to be 88.4 category good in the second cycle. The increasing of the students’ score at first cycle was 18.8% and increase to 42.8% at second cycle.Key words : Learning model, guided inquiry, the result of science